Clinical Manifestations of Systemic Lupus Erythematous in Children at Dr. Hasan Sadikin General Hospital Bandung, Indonesia - Reni Ghrahani; Priya Darshani Ganesan; Reni Farenia Soedjana Ningrat (Faculty of Medicine Universitas Padjadjaran, 2018)
Background: Systemic Lupus Erythematous (SLE) is an autoimmune disease, characterized by production of autoantibodies, leading to damage caused by inflammation, directed toward multiple organs in the body. It is difficult to diagnose due to its mimicry with other diseases. The differential diagnosis of SLE is broad, including infection, malignancy and other inflammatory disorders. It is important to recognize the clinical manifestation of SLE from other possible diseases.Methods: A descriptive study was conducted on 56 SLE patientsfrom the Department of Child Health in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, in which the medical records was collected from 2010 to 2014. A total sampling method was used and incomplete records were excluded.Results: Out of the 56 subjects, 82.1% were female, with female to male ratio was 4.6:1. Most of the subjects (52%) was in the age category of 11 to 15 years old. Hematologic involvement was the most common clinical manifestation based on the diagnostic criteria (83.9%), and fever was the most common chief complaint (41.1%).Conclusions: From this study, fever, rash, and joint pain are the common chief complaints among SLE patients in children with hematologic and renal disorders are also found to occur.